Changes in Motor-Related Cortical Activity Following Deep Brain Stimulation for Parkinson’s Disease Detected by Functional Near Infrared Spectroscopy: A Pilot Study - Morishita, Takashi; Higuchi, Masa-aki; Saita, Kazuya; Tsuboi, Yoshio; Abe, Hiroshi; Inoue, Tooru (Frontiers in Human Neuroscience, 2016)
It remains unclear how deep brain stimulation (DBS) modulates the global neuronal network involving cortical activity. We aimed to evaluate changes in cortical activity in six (two men; four women) patients with Parkinson's disease (PD) who underwent unilateral globus pallidus interna DBS surgery using a multi-channel near infrared spectroscopy (NIRS) system. As five of the patients were right-handed, DBS was performed on the left in these five cases. The mean age was 66.8 ± 4.0 years. The unified Parkinson's disease rating scale (UPDRS) motor scores were evaluated at baseline and 1- and 6-month follow-up. Task-related NIRS experiments applying the block design were performed at baseline and one-month follow-up. The mean of the total UPDRS motor score was 48.5 ± 11.1 in the off-medication state preoperatively. Postoperatively, total UPDRS motor scores improved to 26.8 ± 16.6 (p < 0.05) and 22.2 ± 8.6 (p < 0.05) at 1- and 6-month follow-up, respectively. A task-related NIRS experiment showed a postoperative increase in the cortical activity of the prefrontal cortex comparable to the preoperative state. To our knowledge, this is the first study to use a multi-channel NIRS system for PD patients treated with DBS. In this pilot study, we showed changes in motor-associated cortical activities following DBS surgery. Therapeutic DBS was concluded to have promoted the underlying neuronal network remodeling.